2022
DOI: 10.3389/fpsyt.2022.990660
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy efficacy in adolescents with mental illness: A retrospective comparison

Abstract: BackgroundThere is limited evidence on the efficacy of electroconvulsive therapy (ECT) in adolescents with mental illness. The present study reported outcomes of adolescents with mental illness treated with ECT aimed at providing evidence for large-scale feasibility.ObjectivesThe primary objective of this trial was to examine the differences in demographic and clinical data between responders and non-responders. The secondary objective was to determine whether ECT produced differential readmission rates, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This consistent reduction in risk was particularly stable within the 8 to 12 session range. Though other retrospective studies conducted in different regions of China did not provide the overall average ECT sessions for direct comparison between effective and ineffective groups, they did observe similar disparities (e.g., the effective group averaged 7.4 sessions versus an ineffective group averaged 6.6 sessions, P = 0.046) [ 11 ]. An Israeli retrospective study further emphasized this pattern, revealing that a significant number of patients only responded to treatment after more than 12 ECT sessions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This consistent reduction in risk was particularly stable within the 8 to 12 session range. Though other retrospective studies conducted in different regions of China did not provide the overall average ECT sessions for direct comparison between effective and ineffective groups, they did observe similar disparities (e.g., the effective group averaged 7.4 sessions versus an ineffective group averaged 6.6 sessions, P = 0.046) [ 11 ]. An Israeli retrospective study further emphasized this pattern, revealing that a significant number of patients only responded to treatment after more than 12 ECT sessions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method is capable of significantly reducing both symptoms of depression and the risk of suicide [ 7 ], and its use among teenagers has been consistently growing. Recent retrospective research from various countries has shown that the response rates to ECT for adolescent major depression range from 72 to 78.6% [ 8 11 ]. However, approximately one-third of patients fail to respond to this therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pharmacotherapies can produce more frequent and significant side effects in youth compared to adults, including increased suicide ideation 8 . Meanwhile, Electroconvulsive Therapy (ECT) is prescribed only in rare cases due to safety concerns of seizure induction in the developing brain 9 . Overall, there are few safe, well tolerated, and effective treatment options available for youth with (severe) depression and suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…This method is capable of signi cantly reducing both symptoms of depression and the risk of suicide 7 , and its use among teenagers has been consistently growing. Recent retrospective research from various countries has shown that the response rates to ECT for adolescent MDD range from 72% to 78.6% [8][9][10][11] . However, approximately one-third of patients fail to respond to this therapy.…”
mentioning
confidence: 99%